Proton therapy for head and neck cancer. Issue 3 (May 2015) - Lukens, J. Nicholas; Lin, Alexander; Hahn, Stephen M.
<x xml:space="preserve">Abstract</x> Purpose of review Proton therapy for head and neck cancer is an area of active research as technological advances are increasingly integrated into clinical practice, and also the subject of heightened scrutiny due to the significant associated cost. This article will highlight recent research into proton dosimetry, studies evaluating its clinical benefit relative to other advanced radiotherapy modalities, and key safety and cost considerations. Recent findings Recent dosimetric analyses have quantified the potential for the most sophisticated form of proton therapy, intensity-modulated proton therapy (IMPT), to reduce dose to key anatomic structures in the head and neck, and highlight the potential for dose uncertainty with IMPT if not implemented in a careful manner. Clinical contributions demonstrate the potential for protons to yield excellent local control and lower than expected morbidity for tumors adjacent to critical neurological structures. There are promising data in the reirradiation setting, and emerging data for IMPT in oropharyngeal cancer. Summary Proton therapy for head and neck cancer holds significant potential, and promising single-institution experiences should be validated, wherever feasible, in prospective randomized clinical trials. In light of the significant associated cost, additional evidence is needed to guide the appropriate allocation of patients to IMPT versus intensity-modulated radiotherapy.